2017
DOI: 10.3390/su9091538
|View full text |Cite
|
Sign up to set email alerts
|

Surface Urban Heat Island Analysis of Shanghai (China) Based on the Change of Land Use and Land Cover

Abstract: Abstract:In this paper, we present surface urban heat island (SUHI) analysis of Shanghai (China) based on the change in land use and land cover using satellite Landsat images from 2002 to 2013. With the rapid development of urbanization, urban ecological and environmental issues have aroused widespread concern. The urban heat island (UHI) effect is a crucial problem, as its generation and evolution are closely related to social and economic activities. Land-use and land-cover change (LUCC) is the key in analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 28 publications
2
55
0
2
Order By: Relevance
“…Table 2 shows the accuracy of LCZ's validation, which is calculated by the same method of Estoque et al [24] and Wang et al [11]. The accuracy in all periods are more than 85%.…”
Section: Accuracy Evaluation Of Lczmentioning
confidence: 96%
See 3 more Smart Citations
“…Table 2 shows the accuracy of LCZ's validation, which is calculated by the same method of Estoque et al [24] and Wang et al [11]. The accuracy in all periods are more than 85%.…”
Section: Accuracy Evaluation Of Lczmentioning
confidence: 96%
“…The regression analysis shows that NDVI has a negative correlation with LST, where a low NDVI value is associated with a high LST value. Wang et al [11], Yuwan et al [5], and Ranagalage et al [27] reported that NDVI has negative linear correlation with LST, but it was a weak correlation. It is consistent with our result in this study.…”
Section: Relationship Between Lst and Ndvimentioning
confidence: 99%
See 2 more Smart Citations
“…Within urban climatology, a combination of satellite, aerial, and ground-based thermal remote sensors have been integral in elucidating the spatial [1,2], temporal [3,4], and geometric [5] effects of the built environment on land T surf ; in evaluating and partitioning urban surface energy balances [6][7][8] and; in characterizations of the relationship between surface and boundary-layer air temperatures (T air ) [9]. These advances have been aided by substantial improvements in sensor spatial, spectral, and radiometric resolutions, and by the proliferation and availability of both large-scale satellite remote sensing products and low-cost aerial and near-ground thermography.…”
Section: Introductionmentioning
confidence: 99%